Art of learning for knowledge sharing: a case study of Parisar Asha. (2017) - Misra, Pooja; Gupta, Jaya
The key to effective development of the formative minds is to provide a learning system that enables them to experiment, explore and learn. The early years of life are vital for learning since it lays the foundations for the future. The knowledge and skills acquired in the formative years tend to create a long-lasting impact on the child as he grows up to become responsible citizens of the country. Parisar Asha, a non-profit organisation, seeks to position itself as a change agent in the field of education. There is an effort to modify and translate the standardised learning module into an experiential learning mode which may prove to be instrumental in bringing about their intellectual, social and emotional development. The present case seeks to provide an understanding of environmental-based approach to learning that prepares the groundwork for a creative and value-based orientation for sustainable living.